2014
DOI: 10.1016/j.ccr.2014.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Viral-Human Chimeric Transcript Predisposes Risk to Liver Cancer Development and Progression

Abstract: The mutagenic effect of hepatitis B (HBV) integration in predisposing risk to hepatocellular carcinoma (HCC) remains elusive. In this study, we performed transcriptome sequencing of HBV-positive HCC cell lines and showed transcription of viral-human gene fusions from the site of genome integrations. We discovered tumor-promoting properties of a chimeric HBx-LINE1 that, intriguingly, functions as a hybrid RNA. HBx-LINE1 can be detected in 23.3% of HBV-associated HCC tumors and correlates with poorer patient sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
299
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(313 citation statements)
references
References 35 publications
12
299
2
Order By: Relevance
“…The results of the present study expand on a previous study demonstrating that the chimeric HBx-LINE-1 functions as a hybrid RNA and promotes tumorigenesis in HCC (16). A (20).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of the present study expand on a previous study demonstrating that the chimeric HBx-LINE-1 functions as a hybrid RNA and promotes tumorigenesis in HCC (16). A (20).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it was hypothesized that transcripts of retrotransposons L1 may also influence lung carcinogenesis. The present study focused on the role L1 RNA may serve in lung carcinogenesis without HBV infection, which is different from HBx-LINE-1 causing hepatocarcinogenesis (16). It has previously been demonstrated that L1PA16 RNA binds to PSF protein, which is part of the LINE retrotransposons family (10).…”
Section: Binding Ability Of L1 Rna and Psf Protein In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…2 Hepatitis B virus X protein (HBx) encoded by the X gene of HBV plays a pivotal role in the onset and progression of HBV-associated HCC. 3 HBx can regulate multiple biological events, including cell proliferation, apoptosis, migration and invasion. 4 HBx gene is frequently integrated into the host genome in a 3 0 -end-deleted form, yielding a carboxyl-terminal truncated isoform (ctHBx).…”
Section: Introductionmentioning
confidence: 99%
“…In human breast and colon cancer cell lines, the expression of this LCT was found to be associated with decreased TFPI-2 expression. 9 In hepatitis B virus-positive HCC tissues, Lau et al 70 detected a 674 bp chimeric HBx-L1 transcript that is driven by viral HBx promoter and correlates with unfavorable prognosis of patients. Subsequent functional investigations revealed that HBx-L1 functions as an lncRNA to promote cell mobility in HCC cells through epithelial-to-mesenchymal transition and to promote chemical-induced hepatocarcinogenesis in a mouse model via activation of the Wnt/β-catenin pathway (Figure 2e, bottom).…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%